Effect of different cooking temperature and alkalinity on mechanical and morphological properties of composite sheet from durian shell waste fibre - Munawar, Rose Farahiyan; Arif, Afrana Baiti; Mohamad, Noraiham; Dimin @ Mohd Amin, Mohd Fairuz; Mohd Suan, Mohd Shahadan; Othman, Intan Sharhida; Hasib, Hazman; Abu, Maisarah; Radiman, Shahidan; Mohd Hassan, Nurul Husna (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
Temperature and alkalinity are the critical factors that contribute to the successful of soda pulping. These factors influence the length size and interfibre bonding of the fibre. In this paper, durian (Durio zibethinus Murray) shell composite sheet were prepared by conducting chemical pulping through soda method to study the effect of different pulping temperature and % of NaOH on the mechanical and morphological characteristics of durian shell composite sheet. Six sets of composite sheet were produced from six sets of pulping. The pulping processes were conducted at 140, 160 and 170°C with 17, 19 and 21% of active alkali. The mechanical properties of the durian shell composite sheet were analyzed through few standard TAPPI analyses which are tensile, tear, burst, folding endurance and paper bulk thickness. The results show that the highest reading of paper bulk thickness, tensile, tear and burst index, and also folding endurance were achieved at the pulping condition of 170°C with 21% of NaOH with the value of 1.3366 g/cm3, 54.151 NM/g, 6.648 m.Nm2/g, 2.517 k.Pam2/g and 170 no. of fold, respectively. Scanning electron microscopic analysis showed that morphological changes took place depending on the size and arrangement of the fibres in the composites sheet.